Unravelling the Art of Politeness Strategies in YouTube Content Episode 40 of Johnny’s Communication Center - Faiza Tadzkia; Haryati (Paradigma Lingua, 2025)
The study investigates the application of politeness strategies in digital communication specifically in YouTube content. Using Brown & Levinson’s (1987) politeness theory as a framework, this study analyzes conversational interactions between Johnny and Ten in Johnny’s Communication Center Episode 40: Johnny & Ten Make Kimbap! from NCT Official’s YouTube channel. Through a qualitative descriptive method, the study identifies 63 data that is divided into four types of politeness strategies—bald-on record which is found in 42 data, off-record which is found in 6 data, positive politeness which is found in 15 data, and negative politeness no found in data—and examines the factors influencing their use, such as relative power (10 data) and social distance (53 data). The findings reveal that bald-on record is the most frequently used strategy, reflecting the casual and collaborative dynamic between the speakers. Social distance appears as the most dominant factor affecting strategy choice. This study contributes to the understanding of how politeness operates in informal digital interaction and emphasizes the relevance of pragmatics in media discourse.